Determinants of workplace deviance among manufacturing employee in Malaysia - Chin, Siao Phooi; Chang, Yen Wen; Wong, Danny Fu Keong; Khor, Chang Pin; Low, Su Ying (2019)
The main objective of this study is to examine workplace deviance among employees in manufacturing industry in Malaysia. We have proposed a few hypotheses to examine the relationship between independent variables (perceived organizational support, distributive justice, procedural justice and interactional justice) and dependent variable (workplace deviance). We have also provided the literature review and proposed conceptual framework for this study. In this research, we focus on identify the significant relationship between perceived organizational support and workplace deviance. We also aim to identify significant relationship between organizational justice and workplace deviance. Our target respondents are employees in manufacturing industry in Malaysia. We have collected and analysed data in order to get the result. The result shows that perceived organizational support, distributive justice, procedural justice and interactional justice are significantly correlated with workplace deviance. In short, employers in manufacturing industry should consider perceived organizational support and organizational justice in order to prevent workplace deviance issues.